2021
DOI: 10.1126/sciadv.abe9274
|View full text |Cite
|
Sign up to set email alerts
|

GABA transporter sustains IL-1β production in macrophages

Abstract: Accumulating evidence shows that nervous system governs host immune responses; however, how γ-aminobutyric acid (GABA)ergic system shapes the function of innate immune cells is poorly defined. Here, we demonstrate that GABA transporter (GAT2) modulates the macrophage function. GAT2 deficiency lowers the production of interleukin-1β (IL-1β) in proinflammatory macrophages. Mechanistically, GAT2 deficiency boosts the betaine/S-adenosylmethionine (SAM)/hypoxanthine metabolic pathway to inhibit transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 61 publications
2
50
0
Order By: Relevance
“…Specifically, GABA treatment has been reported to reduce IL-6/IL-12 production in macrophages [39] and impaired phagocytosis of macrophages and monocytic cells [40,72]. However, the GABA transporter GAT2 was recently linked to pro-inflammatory IL-1β secretion in peritoneal macrophages [38]. A recent study showed that activation or blockade of GABA-A Rs influenced the phenotypic characteristics of alveolar macrophages towards classical (M1) or alternative (M2) activation, respectively [73].…”
Section: Role Of Gabaergic Signaling In Immune Activation Of Phagocytesmentioning
confidence: 99%
“…Specifically, GABA treatment has been reported to reduce IL-6/IL-12 production in macrophages [39] and impaired phagocytosis of macrophages and monocytic cells [40,72]. However, the GABA transporter GAT2 was recently linked to pro-inflammatory IL-1β secretion in peritoneal macrophages [38]. A recent study showed that activation or blockade of GABA-A Rs influenced the phenotypic characteristics of alveolar macrophages towards classical (M1) or alternative (M2) activation, respectively [73].…”
Section: Role Of Gabaergic Signaling In Immune Activation Of Phagocytesmentioning
confidence: 99%
“…An increasing number of studies have illustrated the critical roles of GABA transporters (GAT) on health and diseases. Xia et al ( 30 ) showed that GAT2 (SLC6A13) sustained IL-1β production in macrophages, and Ren et al ( 18 ) identified the role of GAT2 in the defense against pathogen infection. This study found that L.lactis reduced GAT2 expression and regulated GABA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, defects in macrophage phenotypic switch, such as the prolonged activation of a pro-inflammatory property in macrophages, are associated with various macrophage-associated diseases ( 117 ). Thus, the significant role of iron in dictating macrophage polarization suggests that iron has potential for affecting the progression of macrophage-associated diseases.…”
Section: Iron In Macrophage-associated Diseasesmentioning
confidence: 99%